Evaluating the Efficacy of Bio-Sanitizer S1 in Disinfecting Contaminated Elastomeric Chains - Mohammed Nahidh (Journal of Global Pharma Technology, 2016)
Background: Special consideration for the elastomeric chains must be paid in order to prevent their contamination. The purpose of this study was to test the efficacy of Bio-sanitizer S1 in disinfection the contaminated elastomeric chains. Materials and methods: Three types of elastomeric chains of short types from three companies were utilized in this study. The as-received elastomeric chains were checked for bacterial and fungal growth using Blood, MacConkey and Sabouraud dextrose agars. Elastomeric chains contaminated by saliva of orthodontic patients were checked for bacterial and fungal growth using the same media. After disinfecting the contaminated elastomeric chains, they were cultured again in the same agars to test the efficacy of Bio-sanitizer S1 as compared to chlorhexidine 0.2%. One-way ANOVA test was used for comparison. Results: As-received elastomeric chains from all companies were free from bacterial and fungal contaminations. The contaminated chains had no growth at all after disinfection with Bio-sanitizer S1 and chlorhexidine. Conclusions: Bio-sanitizer S1 acts as efficacious as chlorhexidine in disinfecting the contaminated elastomeric chains with the disadvantages of longer immersion time associated with the latter.Keywords: Elastomeric chain, disinfection, colony forming units.